STIMULATION OF BALI'S YOUTH GENERATION AWARENESS LEVEL TO SEKEHA TERUNA IN PREVENTING HIV/AIDS SPREADING: A LOCAL GENIUS - BASED COLLABORATIVE ACTION (Proceedings of the International Conference on Public Health, 2022)
HIV/AIDS cases in Bali surge up to 700 in general population according tohealth department data. Sekeha teruna, a local Bali’s youth organization in every hamletcould potentially further optimize its role based on the concern of the Bali’s younggeneration. This study aims to present stimulation of Bali young generation awarenesslevel to role of Sekeha teruna to fend off the spreading of HIV/AIDS in the community ashealth collaborative approach based on local genius. We obtained data throughquestionnaire survey by non-probability sampling technique to 200 young people spreadacross 4 districts in Denpasar City (North, East, South, West) to find the awareness levelpercentage; and in-depth interview with some experts at Komisi Penanggulangan AIDS(KPA) and Kita Sayang Remaja (KISARA), Bali Province about two weeks. Based on theresults of the analysis of research data through a questionnaire survey to people age  18years old, it was found that the dominance of awareness level is quite high (35.9%) andhigh (26.1%). Therefore, it could be the basic foundation of stimulation for the role ofsekeha teruna, especially as spiritual motivators, persuasive and pervasive agent,personality-forming factors and supervisory functions in behavior namely Awareness,Interest, Evaluation, Trial, Adoption (AIETA). Since the high level of awareness,stimulation of Bali’s youth generation to sekeha teruna possess a bright long-term prospectin creating a conducive climate in HIV/AIDS spreading in communities as a public healthcollaborative approach. However, there are still obstacles such as the existence of differentsocial ties, the influence of social media distortion, and there are still young people notjoining the sekeha teruna.
Keywords: local genius, public health, sekeha teruna, HIV/AIDS, AIETA